LARANGAN ISRAF (BERLEBIHAN) DALAM MAKAN DAN MINUM - M. Jefriadi Mais; Ali Akbar; Gusti Muhammad Abdurrahman Yahya Ayyasy (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
This study aims to examine in depth the concept of israf (excess) in the context of food and beverage consumption from an Islamic perspective and its implications for human well-being. Israf, which etymologically means exceeding limits, is a reprehensible behavior expressly prohibited by Allah SWT, as stated in Surah Al-A'raf, verse 31. The method used was library research with a thematic interpretation (maudhu'i) approach and analysis of medical literature related to nutrition and dietary patterns.The results show that the prohibition of israf in eating and drinking encompasses two main dimensions: (1) the Sharia dimension, namely exceeding one's needs and wasting blessings, which can distance oneself from gratitude and make the perpetrator hated by Allah; and (2) the health dimension, namely excessive consumption of food/drinks (both in quantity and quality) which has been medically proven to contribute to various degenerative diseases (such as obesity, diabetes, and heart disease). The concept of moderation (i'tidal) taught by Islam, including proportional portioning of food, serves as a framework for preventing israf behavior, which in turn supports the quality of a Muslim's worship and productivity.